2017
DOI: 10.3390/su9020305
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Different Nighttime Light Data for GDP Estimation at Different Spatial Scales and Regional Levels

Abstract: Abstract:Nighttime light data offer a unique view of the Earth's surface and can be used to estimate the spatial distribution of gross domestic product (GDP). Historically, using a simple regression function, the Defense Meteorological Satellite Program's Operational Linescan System (DMSP/OLS) has been used to correlate regional and global GDP values. In early 2013, the first global Suomi National Polar-orbiting Partnership (NPP) visible infrared imaging radiometer suite (VIIRS) nighttime light data were relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 25 publications
4
65
0
1
Order By: Relevance
“…It can be concluded that at the provincial level, all of the three models are reliable for modeling the long-term GDP dynamics using the extended temporal coverage data. In general, the power function model is the best-fitting model, with the minimum mean MARE value of 14.91%, which is supported by previous studies [17,26]. To further ascertain the most effective provincial-level models, the optimal models for each province were chosen through a comparison of the R 2 and MARE values of each model ( Figure 5).…”
Section: Modeling Results At the Provincial Levelmentioning
confidence: 68%
See 3 more Smart Citations
“…It can be concluded that at the provincial level, all of the three models are reliable for modeling the long-term GDP dynamics using the extended temporal coverage data. In general, the power function model is the best-fitting model, with the minimum mean MARE value of 14.91%, which is supported by previous studies [17,26]. To further ascertain the most effective provincial-level models, the optimal models for each province were chosen through a comparison of the R 2 and MARE values of each model ( Figure 5).…”
Section: Modeling Results At the Provincial Levelmentioning
confidence: 68%
“…Most of the previous studies that modeled the dynamics of the GDP or other socioeconomic parameters using nighttime light data were based on the construction of statistical relationships between TNL and a particular socioeconomic parameter [13,26,37,40,[43][44][45]. By examining the scattergram composed of TNL from the DMSP-OLS and NPP-VIIRS data at the provincial level of China from 2012 to 2013, which is the overlap period when the nighttime light data were collected by both sensors, we were able to observe sharply defined diagonal clusters of points ( Figure 1a).…”
Section: Temporal Coverage Extension Of the Nighttime Light Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [31] proposed a simple and approximate process for removing the confounding factors by using DMSP-OLS data. This method has been recognized by many scholars [13,27,30,42]. However, the spatial resolution of DMSP-OLS data and NPP-VIIRS data are quite different.…”
Section: Discussionmentioning
confidence: 99%